The Impact of Diet on Performance in Endurance Sports - Literature Review - Broda, Aleksandra; Hoksa, Kacper; Dubniewicz, Ewa; Majewska, Paula; Staszek, Alicja; Łoskot, Wiktoria; Szwech, Jan; Matczak, Mateusz; Jasiński, Karol; Jodłowski, Krzysztof (Quality in Sport, 2025)
Introduction: The physical performance of athletes in endurance disciplines is the result of a complex process of the body adapting to prolonged and intense exertion. A significant factor influencing the efficiency of this process is an appropriate diet, which ensures optimal conditions for maintaining performance, recovery, and achieving maximum results during competitions. The diet of an athlete, especially in endurance sports, plays a crucial role in providing adequate amounts of energy, micronutrients, and macronutrients, such as carbohydrates, fats, and proteins, which are necessary to maintain energy levels, especially during prolonged efforts. Proper dietary balance, including an adequate supply of carbohydrates, affects the body’s ability to utilize stored energy resources and facilitates post-exercise recovery mechanisms. Objective: To review available studies on the impact of diet on the physical performance of endurance athletes, analyze the findings, and draw practical conclusions that can be used to create dietary plans for athletes. Current Knowledge: Athletic performance is the body’s ability to perform physical exertion for an extended period without excessive fatigue while maintaining adequate efficiency. It depends on the cardiovascular, respiratory, and muscular systems’ ability to deliver energy and remove metabolic by-products. Diet has a significant impact on the body’s performance, and both the number of calories consumed and their primary source are critical for athletic achievements